Genetic surveillance of first- and second-line drug-resistant isolates of Mycobacterium tuberculosis in Peru - David Santos-Lázaro; Aiko N. Vigo; Vidia V. Cotrina; Sandra Villar; Alexis Medina; Cynthia Julcapoma; Edson Pacheco; Miriam J. Alarcón; Zully M. Puyén (PLoS ONE, 2026)
Tuberculosis (TB) remains a critical public health crisis in Peru, which bears the highest multidrug-resistant TB (MDR-TB) burden in the Americas. The objective of this study was to conduct a nationwide genetic surveillance of first- and second-line drug-resistant Mycobacterium tuberculosis isolates in Peru to characterize their structural and geographic distribution using a multilocus genotype approach. We analyzed 38,339 valid results from first- and second-line line probe assays (LPA 1L, GenoType MTBDR plus v2; and LPA 2L, GenoType MTBDR sl v2) routinely collected between 2019 and 2022 by the Peruvian National Institute of Health. First-line (G1) and second-line (G2) multilocus genotypes were generated by concatenating specific hybridization banding patterns across resistance-associated loci. Additionally, targeted next-generation sequencing was performed on a stratified proportional sample of 170 isolates exhibiting “inferred” resistance genotypes, defined by a missing wild-type signal without a corresponding mutant probe, to elucidate their underlying mutational profiles. Resistance genotypes were identified in 13.5% and 11.8% of LPA 1L and LPA 2L results, respectively. The genotypic landscape was highly concentrated: 13 dominant G1 genotypes and 19 dominant G2 genotypes accounted for over 85% of their respective resistant cohorts. Structurally, these dominant genotypes mainly carried globally successful, canonical mutations (e.g., katG S315T1, rpoB S450L). Geographically, dominant genotypes were heavily consolidated within the hyper-endemic central coastal axis (Lima, Callao, and Ica) and the Amazonian department of Ucayali, maintaining highly stable temporal frequencies. Conversely, heteroresistance and complex multi-mutational patterns were exclusively restricted to low-frequency rare and orphan genotypes. Targeted sequencing of inferred patterns successfully expanded the national catalog of resistance variants, identifying non-canonical determinants (e.g., inhA g-17t, gyrB T500N) and preventing false-positive resistance calls driven by synonymous mutations. This large-scale mapping demonstrates that Peru’s drug-resistant TB epidemic is characterized by the widespread consolidation of a restricted number of canonical multilocus genotypes. Integrating targeted sequencing with routine molecular screening is essential to resolve unclassified hybridization patterns and optimize epidemiological management in high-burden settings.